When to puncture, when not to puncture: Pancreatic masses - Iglesias-Garcia, Julio (Medknow Publications & Media Pvt Ltd, 2014)
Endoscopic ultrasound (EUS) has evolved to become a crucial tool for the evaluation of pancreatic diseases, among them solid pancreatic lesions. However, its ability to determine whether a lesion is malignant or not is difficult to establish based only in the endosonographic image. EUS-guided fine needle aspiration (EUS-FNA) allows obtaining a cytological and/or histological sample from pancreatic lesions, with a high overall accuracy and low complication rates. Although the clinical usefulness of EUS-FNA for pancreatic diseases is widely accepted, the indications for tissue diagnosis of pancreatic lesions suspected to be malignant is still controversial. This review highlights the diagnostic accuracy and complications of EUS-FNA, focusing on its current indications.